Social Reality in the Novel Kereta Semar Lembu (Georg Lukacs' Study of Socialist Realism) - Kemala Sari, Dea; Kurnia Rachmawati; Arju Susanto (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
This research aims to describe objective reality, dialectical movements and emancipatory critical expressions in the novel Kereta Semar Lembu using Georg Lukacs' socialist realism theory. This research uses a qualitative descriptive method with the literary sociology approach of Georg Lukacs. Data collection techniques used include reading, taking notes and conducting literature studies. The data analysis technique in this research is descriptive analysis. The results of this research found that there is social reality 1) objective reality is reflected through the phases of oppression during colonial rule, Japanese colonialism and the era of independence, with people suffering as a result of inhumane colonial policies, 2) the dialectical movement in this novel plays a crucial role in understanding the dynamics of history and social change, seen through workers' resistance, the struggle for independence, and the difficulty of achieving peace between the Republic of Indonesia and the Kingdom of the Netherlands, 3) emancipatory critical expressions are reflected in various forms of resistance, showing the critical spirit of the figures in facing colonialism and inequality at that time.